(untitled) (International Seven Journal of Health Research, 2023)
Gallbladder polyp is an elevation of the gallbladder wall that can be classified into different types. Cholesterol polyps are the most common, followed by inflammatory and adenomatous polyps. Polyps are usually asymptomatic, but they can cause abdominal pain, nausea, and other symptoms in some cases. The diagnosis is made by imaging tests, such as abdominais ultrasonography, which is the preferred method due to its accuracy and low cost. Polyps larger than 1 cm, symptomatic or in patients with risk factors, usually require cholecystectomy (removal of the gallbladder). Some polyps can be malignant, such as adenocarcinoma, which is more common in polyps larger than 1cm. Papillary neoplasms of the biliary tract, such as cholangiocarcinoma, may also be associated with vesicular polyps. Management and prognosis depend on the type and characteristics of polyps found. The case report in question brings Videolaparoscopic Cholecystectomy as a treatment choice, based on the benefits and indications of the technique.